The Urgency of Forensic Linguistics in a Police Interrogation Process - Apriyanto, Sigit; Dalman; Santoso, Dwi (International Journal of Psychosocial Rehabilitation, 2020)
Forensic linguistic experts identify problems through a speech from speakers in the form of language style, forensic phonetics, and dialectology while writing in the form of fingerprints and analysts to express the contents of their writing. Orally, these problems can be found in utterances of hatred, hoaxes, defamation, and honesty of speakers while writing a letter, notes of suicides, and fingerprints. In the forensic linguistic level, it has the scope to examine every problem in the field of law including pragmatics, semantics, discourse analysis, and phonetics. The focus of this paper is to review the urgency of the role of forensic linguists in the process of analysing the results of police interrogation in Indonesia. Data collection in this study uses the literature study method. The data collected were analysed using descriptive analysis method. In this paper, the things related to the role of linguistic forensics will be presented in the process of interrogation, legal language, and forensic linguistic position itself. Finally, the service of an interpreter and found that the points of view of the interpreter, sociolinguistics and interpreting studies can be an excellent source of knowledge in reading this case. Therefore, in interpreting a text it should highlight the construction of the language thoroughly. It is because each type of document has a different structure and context.